Molecular simulation studies of AMP/MDEA absorption process for CO2 capture - Nur Alia Adnin, Zainol Abidin (2015)
Carbon capture using post-combustion technology is the most mature technology nowadays. Post-combustion process is based on the absorption process with a solution of Nmethyldiethanolamine (MDEA) 30wt. % in water. However, despite the advantages of MDEA which have higb1y efficient energy utilization, there have been some drawbacks especially the low reactivity with C02 during the absorption process. For this reason, there is a need to innovate and optimize solvents fur C02 capture in order to improve the solvent capture efficiency. This work focuses on the blended amine using 2-amino-2-methyl 1-propanol (AMP) and MDEA. The aim of this study is to perform molecu1ar dynamic simulation using Material Studio software to give insight on this process at molecu1ar level Process operating conditions (obtained from previous research) is used to set the process condition i.e. pressure, temperature and concentration in Material Studio software. The intermolecu1ar interaction is analyzed in terms of radial distribution function which would determine the intermolecu1ar interactions in the solution. It is expected that this study will give more insight and understanding on C02 absorption process for further improvement and suggestion for development of new solvent.